2019
DOI: 10.5005/jp-journals-10024-2541
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cervical Vertebral Bone Age and Demirjian's Stages of Dental Maturation for Lower Left Permanent Canine and Second Molar

Abstract: Aim: To evaluate and correlate cervical vertebral bone age(CVBA) and Demirjian's stages of dental maturation for lower left permanent canine(CMS) and second molar (MMS). Materials and methods: A cross-sectional radiographic study was conducted on 264 participants with age group of 7-18 years who were further categorized into six subgroups having an interval of 2 years chronologic age. The CVBA, CMS, and MMS were assessed for the same patient. The assessment of CVBA of the participants involved in the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Uysal et al 27 evaluated the relationship between chronological age and CVM and reported that a high correlation coefficient was found between chronologic age and CVM, and a high correlation was also found in both sexes, although it was significantly better for females. On the other hand, Kulkarni and Dave 28 stated that there was a moderate correlation between chronological age and cervical vertebral bone age. In another study that investigated the effect of CVM age estimation via panoramic radiographs 6 noticed that the R 2 value of CVM was found to be 46%.…”
Section: Discussionmentioning
confidence: 99%
“…Uysal et al 27 evaluated the relationship between chronological age and CVM and reported that a high correlation coefficient was found between chronologic age and CVM, and a high correlation was also found in both sexes, although it was significantly better for females. On the other hand, Kulkarni and Dave 28 stated that there was a moderate correlation between chronological age and cervical vertebral bone age. In another study that investigated the effect of CVM age estimation via panoramic radiographs 6 noticed that the R 2 value of CVM was found to be 46%.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sato et al found that mandibular growth potential could be accurately assessed based on CVBA, which was useful in planning the timing of treatment, and treatment options in patients with class 3 malocclusions [ 25 ]. Studies have also shown that CVBA is correlated with dental eruption [ 26 ] and dental maturation of the lower permanent canine and second molar [ 27 ]. This can aid in orthodontic treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…The ruler and other physically measured linear measurements were used to establish a magnification scale for the subsequent photogrammetric analysis Digital photographs were analyzed, and measurements were performed using IC Measure version 2.0.0.245 and Rhinobase (2000-2001), both with a track-record of clinical reliability. [15][16][17] Linear and angular measurements as well as ratios were performed on anterior (Figure 3, Table 1), lateral (Figure 4, Table 2) and basal views (Figure 5, Table 3).…”
Section: Materials Apparatus and Equipmentmentioning
confidence: 99%